Estimating the rate of retinal ganglion cell loss to detect glaucoma progression: An observational cohort study. Issue 30 (July 2016) - Hirooka, Kazuyuki; Izumibata, Saeko; Ukegawa, Kaori; Nitta, Eri; Tsujikawa, Akitaka
Abstract : Abstract: This study aimed to evaluate the relationship between glaucoma progression and estimates of the retinal ganglion cells (RGCs) obtained by combining structural and functional measurements in patients with glaucoma. In the present observational cohort study, we examined 116 eyes of 62 glaucoma patients. Using Cirrus optical coherence tomography (OCT), a minimum of 5 serial retinal nerve fiber layer (RNFL) measurements were performed in all eyes. There was a 3-year separation between the first and last measurements. Visual field (VF) testing was performed on the same day as the RNFL imaging using the Swedish Interactive Threshold Algorithm Standard 30–2 program of the Humphrey Field Analyzer. Estimates of the RGC counts were obtained from standard automated perimetry (SAP) and OCT, with a weighted average then used to determine a final estimate of the number of RGCs for each eye. Linear regression was used to calculate the rate of the RGC loss, and trend analysis was used to evaluate both serial RNFL thicknesses and VF progression. Use of the average RNFL thickness parameter of OCT led to detection of progression in 14 of 116 eyes examined, whereas the mean deviation slope detected progression in 31 eyes. When the rates of RGC loss were used, progression was detected in 41 of the 116 eyes, with a mean rate of RGC loss of −28, 260 ± 8110 cells/year. Estimation of the rate of RGC loss by combining structural and functional measurements resulted in better detection of glaucoma progression compared to either OCT or SAP.